The Landscape of Middle English Focusing on the Adverb Even - Olena Andrushenko (Litera: Dil, Edebiyat ve Kültür Araştırmaları Dergisi)
The study is aimed at exploring adverb even as the information structural component, viz., a Focus marker in Middle English records based on the Corpus of Middle English Prose and Verse. Functioning as an adverb already in Old English (OE), Middle English (ME) provides evidence to gradual transformation of even into an additive marker according to the following pattern: OE degree/manner adverb→ME restrictive particularizer→ME restrictive exclusive→ME scalar additive. The latter meaning in Present-Day English can be singled out on the ground of such semantic criteria of the Focus phrase as [+likelihood], [+additivity], [+scalar], [+givenness] and [+surprise]. The three types of focusing even registered in Middle English texts are analyzed in terms of information novelty and various Foci types marked by the adverb, as well as, syntactic arrangement of sentence constituents. Corpus studies revealed that depending on the sense, even pertains to a specific Focus type and may cause word order to change. Specifically, when the adverb is used in its Present-Day English meaning, it highlights predominantly mirative Focus, and the analysis of word order patterns indicates the fronting of X-element in the clause, which may be put down to the fact that this scalar additive stresses surprising or unusual context for the reader. Therefore, inverted arrangement of elements may be used for stylistic purposes.